Innovative Strategies for Nurse Manager Performance Assessment: A Literature Review - Yunita, Sukma; Pasaribu, Masdalifa; Sharfina, Dirayati; Fauziah Silalahi, Yetti; Leini Saragih, Srimis (Universitas Haji Sumatera Utara, 2025)
The nursing management field encompasses a range of responsibilities and roles, including overseeing staff, coordinating patient care, managing budgets, and ensuring quality and safety standards are met (Mitchell et al., 2022). The nursing management field involves overseeing staff, coordinating patient care, managing budgets, and ensuring quality and safety standards (Kinshella et al., 2020). Factors such as understaffed units and high turnover rates can hinder effective training (Kinshella et al., 2020). Improving service quality, working conditions, and management of the nursing workforce are crucial for fostering good nurse-client relationships (Isangula et al., 2022). Enhancing nursing students' presentation competencies can prepare them to address complex health challenges through critical thinking and effective communication (Haramba, 2023). Implementing programs like the